Efek Program Movement Education Model pada Perkembangan Fundamental Movement skill siswa - Jajang Nurjaman; Edi Setiawan; Adi Rahadian; Ervan Kastrena; Deddy Whinata Kardiyanto; Ruslan Abdul Gani (Jurnal Sporta Saintika, 2022)
This research is motivated by the low fundamental movement skills possessed by students today. The purpose of this study is to examine the effect of the movement education model program on improving fundamental movement skills. The method in this research is experimental with the use of one group pre-test and post-test design. The subjects came from 101 students at Al-Azami Junior High School, then they were selected in a random cluster and the students in grades VII-A and VIII-B were selected (N=41). The Fundamental Movement Skill instrument uses locomotor, object-control and stability tests. The movement education model intervention program was carried out for 9 meetings. Data analysis using the SPSS application which aims to find the minimum, maximum, mean and standard deviation, normality, homogeneity and paired sample t-test values. The main findings show that there is an influence of the movement education model on the improvement of fundamental movement skills (P <0.05). Thus, it can be concluded that the movement education model learning that is integrated into physical education is proven to be able to change fundamental movement skills for the better than before.